Partisipasi Masyarakat Lokal Tanjungbalai dalam Pengembangan Objek Wisata Waterfront City, Kelurahan Indera Sakti, Kecamatan Tanjungbalai Selatan, Kota Tanjungbalai - Alfindo Tri Givana; Ema Sry Lestari Br Nahampun; Pristi Suhendro Lukitoyo (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
This research is motivated by the emergence of a new tourist attraction in the city of Tanjungbalai. This study aims to see how the participation of local communities in the development of the Waterfront City Tanjungbalai tourism object. The method used is observation and interviews with tourists and local communities as well as using literature studies from various literatures. The results of the study concluded that the participation of local communities in this tourist attraction was very high. This can be seen from the large number of local people's participation in developing tourist attractions by selling various kinds of souvenirs and providing transportation that can be accessed by visiting tourists. However, there is no visible participation in other matters such as less attractive tourist attractions.